Approximation by q-Bernstein-Stancu-Kantorovich operators with shifted knots of real parameters - Mursaleen, Mohammad Ayman; Kilicman, Adem; Md., Nasiruzzaman (Faculty of Sciences and Mathematics, University of Nis, Serbia, 2022)
Our main purpose of this article is to study the convergence and other related properties of q-Bernstein-Kantorovich operators including the shifted knots of real positive numbers. We design the shifted knots of Bernstein-Kantorovich operators generated by the basic q-calculus. More precisely, we study the convergence properties of our new operators in the space of continuous functions and Lebesgue space. We obtain the degree of convergence with the help of modulus of continuity and integral modulus of continuity. Furthermore, we establish the quantitative estimates of Voronovskaja-type.